The Establishment of The Character Of Indonesian Surrounding through Techniques of Folklore Helpful Value Clarification in Pontianak Primary School - Marzuki Marzuki; Sri Utami (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2018)
This study aims to form the characters of Indonesian students through the implementation of Value-clarified Techniques with the help of folklore. The implementation of this lesson is based on the dynamics and problematics of characters that occur today in primary schools and intends to bridge the issues. The research design used is the type of action research with the subject of the study of grade V of Pontianak Elementary School Pontianak amounted to 32 people in the first semester. Data collection methods are observation and interview, while to analyze the data with qualitative descriptive. From the analysis of the results of research and discussion obtained the conclusion that the implementation of Value-assisted Clarification Technique folklore can improve the formation of the character of Indonesian students in primary schools.